2017
DOI: 10.1097/coc.0000000000000183
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Significance of Pretreatment Hematologic Parameters in Patients Undergoing Resection for Colorectal Cancer

Abstract: Pretreatment lymphopenia, thrombocytosis, a decreased lymphocyte-to-monocyte ratio, and an elevated neutrophil-to-lymphocyte ratio independently predict for worse OS in patients with CRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 32 publications
(26 reference statements)
8
34
0
Order By: Relevance
“…The cutoff value for LMR varies widely in different studies, from 2.14 (68) to 3.78 (69). Some authors calculated the cutoff value for LMR very close to that of our study (2,28,70,71). The literature data regarding the prognostic value of the PNI index seem to be the most consistent.…”
Section: Discussionsupporting
confidence: 85%
“…The cutoff value for LMR varies widely in different studies, from 2.14 (68) to 3.78 (69). Some authors calculated the cutoff value for LMR very close to that of our study (2,28,70,71). The literature data regarding the prognostic value of the PNI index seem to be the most consistent.…”
Section: Discussionsupporting
confidence: 85%
“…The majority of reports have shown NLR to be a novel biomarker of survival in primary and metastatic colorectal cancers [30,31,32,33,34,35,36]. A meta-analysis combining results from 49 studies containing 14,282 patients showed that higher values of NLR were associated with poor disease-free [hazard ratio (HR): 1.99; 95% CI = 1.80-2.20; p < 0.001] and overall survival (HR: 1.92; 95% CI = 1.64-2.24; p < 0.001) in solid cancer patients [2].…”
Section: Discussionmentioning
confidence: 99%
“…This finding may be related to the presence of chronic inflammation that is associated with decreased cell growth control capacity, which leads to genomic destabilization by the production of reactive oxygen species (hydrogen peroxide (H 2 O 2 ), singlet dioxygen (1O 2 ), and hydroxyl radical (HO)) and nitrogen compounds (molecules derived from nitric oxide (NO) and superoxide (O 2 2)) due to the action of phagocytic cells. 6,34,46 The significant association between gene expression and DNA repair proteins and expression of inflammatory markers (IL-2 and TNF-a genes) reinforced the idea that chronic inflammation plays a decisive role in Table 5. Association between the expression of inflammatory marker genes-mRNA-(TNF-a, IL-2, and IL-10) with the expression of MMR genes-mRNA-(hMLH1, hMSH2, hMSH6, and PMS2) in patients with colorectal carcinoma.…”
Section: Discussionmentioning
confidence: 86%
“…4,5 A previous study showed that inflammation alters immunity and normal cell proliferation, which can result in the loss of cellular growth control capacity, favoring genomic destabilization and consequent development of neoplasms. 6 Malignant neoplasms, such as colorectal adenocarcinoma, arise in association with chronic inflammation, which induces irreversible and persistent somatic changes in DNA in normal colonic tissue. 2,4,7 This state remains until a second stimulation occurs after colon cells are exposed to chronic inflammation, which then recruits inflammatory cells, induces cell proliferation, and produces reactive oxygen species.…”
Section: Introductionmentioning
confidence: 99%